Every breath - Sparks, Nicholas; Michael, Sean Cameron, 1969-; Johansson, Vanessa, 1980- (New York Hachette Audio, 2018)
Hope Anderson is at a crossroads. At thirty-six, she's been dating her boyfriend, an orthopedic surgeon, for six years. With no wedding plans in sight, and her father recently diagnosed with ALS, she decides to use a week at her family's cottage in Sunset Beach, North Carolina, to ready the house for sale and mull over some difficult decisions about her future. Tru Walls has never visited North Carolina but is summoned to Sunset Beach by a letter from a man claiming to be his father. A safari guide, born and raised in Zimbabwe, Tru hopes to unravel some of the mysteries surrounding his mother's early life and recapture memories lost with her death. When the two strangers cross paths, their connection is as electric as it is unfathomable ... but in the immersive days that follow, their feelings for each other will give way to choices that pit family duty against personal happiness in devastating ways.
Title from web page.
Compact discs.
Read by Sean Cameron Michael and Vanessa Johansson, with an introduction read by Nicholas Sparks.
107254
Keywords: Amyotrophic lateral sclerosis -- Fiction; Man-woman relationships -- Fiction; Fiction -- Romance -- Contemporary; Fiction -- Family Life; Man-woman relationships; Sunset Beach (N.C.) -- Fiction; North Carolina -- Sunset Beach; Domestic fiction; Audiobooks; Fiction; Love stories; Romance fiction